Human cell surface glycoprotein related to cell proliferation is the receptor for transferrin. - Trowbridge, I S (1981)
A cell surface glycoprotein antigen with an apparent molecular weight of about 100,000 that is selectively expressed on proliferating cells was purified from deoxycholate-solubilized membranes of a cultured human leukemic thymus-derived (T) cell line by affinity chromatography on a monoclonal antibody-Sepharose column. A conventional xenoantiserum prepared by immunization with the affinity-purified glycoprotein was found to contain antibodies against a serum component that bound tightly to cultured cells. This molecule was shown to be specifically associated with the cell surface glycoprotein purified by immunoprecipitation from lysates of cells. We have identified the serum component as transferrin and conclude that the membrane glycoprotein is the cell surface transferrin receptor.